Sports in America : recreation, business, education, and controversy - Meyer, Stephen (Farmington Hills, MI : Gale, Cengage Learning, 2016)
Explores the role of sports in American society. Covers participation and attendance at sporting events; the sports industry; illegal gambling and performance-enhancing drugs; and student athletes.
Chapter 1. Sports in American society : an overview -- chapter 2. Sports participation and attendance -- chapter 3. Sports and the media -- chapter 4. Professional team sports -- chapter 5. Other professional sports -- chapter 6. College, high school, and youth sports -- chapter 7. The Olympics -- chapter 8. Sports and health -- chapter 9. Performance-enhancing drugs -- chapter 10. Sports and gambling.
"ISSN: 1557-5535."
Includes bibliographical references and index.
Keywords: Sports -- United States